Floristic diversity apple forests at monitoring sites of the Ile-Alatau National Park (Experimental biology, 2016)
The results of perennial investigations in the Ile-Alatau National Park on the composition of apple forests flora at five monitoring sites are summarized in this article. The authors give a brief description of these sites, a common list of flora, which includes 219 species from 155 genera and 55 families, and indicate the degree of abundance of each species on a specific site. The authors determined from the analysis of the floristic composition that the leading position (65%) occupy the first 10 families and as well described the most typical representatives of the communities. 28 species, including 4-of trees and bushes and 24 herbaceous plants are constant companions of apple trees. Five species listed in the Red Book of Kazakhstan, two (Eremurus robustus, Clinopodium integerrimum) need in regional protection. From invasive and weed species 10 are the most noteworthy, from which the status of separated populations (Artemisia annua, A. tournefortiana) are very unstable.
Keywords: apple forest; flora; species; rare; relict; weed.